The concept of carbon accounting in manufacturing systems and supply chains - Kaur, Rashmeet; Patsavellas, John; Haddad, Yousef; Salonitis, Konstantinos (MDPI, 2024)
Carbon accounting is primarily a process for measuring, reporting, and allocating greenhouse gas emissions from human activities, thus enabling informed decision-making to mitigate climate change and foster responsible resource management. There is a noticeable upsurge in the academia regarding carbon accounting, which engenders complexity due to the heterogeneity of practices that fall under the purview of carbon accounting. Such plurality has given rise to a situation where diverse interpretations of carbon accounting coexist, often bereft of uniformity in definition and application. Consequently, organisations need a standardised, comprehensive, and sequentially delineated carbon accounting framework amenable to seamless integration into end-to-end manufacturing systems. This research commences with the progressive evolution of the conceptual definition of carbon accounting. Then, it delves into the current state of carbon accounting in manufacturing systems and supply chains, revealing gaps and implementation issues warranting future scholarly exploration.
Keywords: carbon accounting; emissions accounting; greenhouse gas emissions; environmental accounting; sustainable manufacturing systems; net-zero